بناء مقياس تقدير لتشخيص صعوبات تعلم الرياضيات لذى تلاميذ سنة الثالثة ابتدائي - شوية,حسنية; الاطرش,فاطمة (University of Eloued جامعة الوادي, 2024)
The current study aimed to construct a diagnostic evaluative scale for mathematics learning difficulties among third-grade elementary students from the perspective of teachers. The study adopted a descriptive approach, selecting a random sample of (347)students of El Oued. The dimensions and items of the scale were adjusted, and psychometric properties were calculated to determine the extent to which this scale meets the conditions of good testing. The following specialist methods were used to verify this: Pearson correlation coefficient to verify validity Cronbach's alpha coefficient to verify reliability Calculation of differences to ensure discriminant validity The study reached the following results: The scale dimensions demonstrated a high level of internal consistency reliability (construct validity). The scale exhibited high levels of self and discriminant validity. The scale dimensions showed high stability indicators. Criterion-referenced standards were extracted, based on which raw scores were interpreted for standardization هدفت الدراسة الحالية إلى بناء مقياس تقدير لتشخيص صعوبات تعلم الرياضيات لدى تلاميذ السنة الثالثة ابتدائي، اعتمدت الدراسة على المنهج الوصفي الاستكشافي، تم اختيار عينة عشوائية بواقع(347) تلميذ وتلميذة على مستوى بلدية الوادي. تم ضبط ابعاد وبنود المقياس وحساب الخصائص السيكو مترية لمعرفة مدى توفر هذا المقياس على شروط الاختبارات الجيدة. من خلال ايجاد: - صدق المحتوى. - صدق الاتساق الداخلي باستخدام معاملات الارتباط بيرسون. -الصدق التمييزي باستخدام (T.test). - دلالات الثبات باستخدام طريقتين: - معامل "الفا كرونباخ". - معادلة "سبيرمان براون" وتم تعديل النتائج بـمعادلة "جيتمان". وتوصلت الدراسة الى النتائج التالية: -تمتع أبعاد المقياس بدرجة عالية من صدق الاتساق الداخلي (صدق البناء). -تمتع المقياس بدرجة مرتفعة التمييزي. -تمتع ابعاد المقياس بمؤشرات ثبات مرتفعة. -تم استخراج معايير الأداء المئينية التي في ضوئها تم تفسير الدرجات الخام لعينة التقنين.
Keywords: صعوبات التعلم; التشخيص; الرياضيات; diagnosis; learning difficulties; mathematics